Strategi Pemasaran terhadap Pencapaian Target Kredit Usaha Rakyat di Bank Jawa Tengah Cabang Brebes - Hesti Karuniati Rizkiana; Dumadi Dumadi; Hendri Sucipto; Slamet Bambang Riono (BADAN PENERBIT STIEPARI PRESS, 2025)
This study aims to evaluate the marketing strategies implemented by Bank Jateng, Brebes Branch, in achieving the 2024 target for the distribution of People’s Business Credit (KUR). KUR is a crucial financial program designed to stimulate the growth of Micro, Small, and Medium Enterprises (MSMEs), making effective marketing strategies essential for its success. This research adopts a descriptive approach, utilizing data collection techniques such as interviews, observations, and documentation from bank officials and KUR-receiving MSMEs. The marketing strategies analyzed include digital marketing, product adjustments to suit local needs, effective communication with prospective customers, and improvements in customer service. The findings reveal that internal factors contributing to the success of marketing strategies include disciplined promotional implementation, competitive low-interest rate offerings, and fast, responsive service. External factors supporting success include direct promotions in public areas such as traditional markets, support from local governments, and stable economic conditions. Direct marketing strategies, such as canvassing and leveraging referrals from existing customers, effectively enhanced customer loyalty and expanded the reach to potential KUR recipients. Furthermore, the use of digital media—such as social media platforms, chatbots, and geotargeted advertising—significantly accelerated communication, increased product visibility, and raised public awareness of the benefits of KUR. The combination of digital and personal approaches proved to be an efficient and effective strategy in reaching broader market segments. Overall, the integration of adaptive and comprehensive marketing strategies has made a significant contribution to increasing the volume of KUR distribution at Bank Jateng, Brebes Branch. This supports the strengthening of the local economy, expands access to inclusive financial services, and reinforces the role of MSMEs as the backbone of regional economic development.